2017
DOI: 10.1002/rra.3128
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Head Dam Impacts on Habitat and the Functional Composition of Fish Communities

Abstract: The natural flow regime of many rivers in the USA has been impacted by anthropogenic structures. This loss of connectivity plays a role in shaping river ecosystems by altering physical habitat characteristics and shaping fish assemblages. Although the impacts of large dams on river systems are well documented, studies on the effects of low‐head dams using a functional guild approach have been fewer. We assessed river habitat quality and fish community structure at 12 sites on two rivers; the study sites includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Analyzing the thermal effects of beaver dams, Weber et al (2017) found a complex and diverse range of temperature responses. Similarly, some authors find little to no thermal influence of beaver dams (Sigourney et al, 2006), and others find extreme temperature increases of up to 7 • C in a headwater passing through large (5 ha) beaver dam complexes (Margolis et al, 2001).…”
Section: Small Dam Thermal Effectsmentioning
confidence: 99%
“…Analyzing the thermal effects of beaver dams, Weber et al (2017) found a complex and diverse range of temperature responses. Similarly, some authors find little to no thermal influence of beaver dams (Sigourney et al, 2006), and others find extreme temperature increases of up to 7 • C in a headwater passing through large (5 ha) beaver dam complexes (Margolis et al, 2001).…”
Section: Small Dam Thermal Effectsmentioning
confidence: 99%
“…They are often built for water consumption and agricultural irrigation and may modify local habitat conditions in streams by causing such effects as water deepening, velocity changes, and substrate‐size decreasing in impoundments and may further alter the composition and abundance of local fish assemblages (Gillette, Daniel, & Redd, ; Yan, Wang, Zhu, Chu, & Chen, ). The degree to which fish assemblages are affected depends on dam size and function (Li, Zhang, et al, ), landscape conditions (Wang, Infante, Lyons, Stewart, & Cooper, ), the identity of the fish species and their behaviours (Smith, Meiners, Hastings, Thomas, & Colombo, ), and the size of the spatial scale and diversity index values (Fencl, Mather, Smith, & Hitchman, ). In addition, habitat modifications associated with dam impoundment may not only impact the indigenous fishes (Marchetti & Moyle, ) but also create favourable conditions for some cosmopolitan fishes, including “alien invasive species” (i.e., from other biogeographic regions) and “native‐invasive species” (i.e., from the same region but other locations; Chu et al, ; Rahel, ; Scott & Helfman, ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of small dams in streams is known to outweigh by several orders of magnitude that of large dams (> 15 m) (Downing et al, 2006;Poff and Hart, 2002;Verpoorter et al, 2014). Paradoxically, their effect on the thermal regime is much less well known and little documented as such (Downing, 2010;Ecke et al, 2017;Smith et al, 2017). This is challenging to identify and generalize the significant drivers of a realistic thermalscape (Isaak, 2017), an essential knowledge 250 to understand the current ecological status of rivers and to predict with sufficient realism future changes with different Hydrol.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the effect of small dams on temperature has been little studied, either in isolated case studies (one stream, Kornis et al, 2015;Majerova et al 2015;Smith et al 2017;Weber et al 2017), often as a secondary variable and with incomplete information about the characteristics of dams (Kemp et al, 2012).…”
Section: What Physical Variables Are Important?mentioning
confidence: 99%